Comunicação e consumo midiático: estratégias da extrema direita nas eleições de 2022 - Silva, Victória Araújo Lago (2024)
This study analyzes media consumption and digital communication in the face of the contemporary political scenario, more specifically, the far-right elections. We analyzed, using the strategy mapping methodology, how, based on a work that addresses the growth of the contemporary far-right (Os Engenheiros do Caos - Da Empoli, 2019), it is possible to identify several communication strategies that are used simultaneously in different poles, including in the Brazilian presidential elections in 2022. Thus, we seek to understand the existence of a common communication plan among the agents and main personalities of the global far-right, using the digital account of former candidate Jair Bolsonaro on the former Twitter (now X) as a starting point for an analysis of identification of the strategies recognized in the base work. In an attempt to explain this process that is based on the consumption of digital media, we use as theoretical bases the contributions of Isleide Fontenelle, Roger Silverstone, Byung chul Han, among other authors who contributed to the understanding of the digital nvironment and the contemporary neoliberal model, which situates the present research.